Monocyte Count and 30-Day Case Fatality in Intracerebral Hemorrhage. Issue 8 (August 2015) - Walsh, Kyle B.; Sekar, Padmini; Langefeld, Carl D.; Moomaw, Charles J.; Elkind, Mitchell S.V.; Boehme, Amelia K.; James, Michael L.; Osborne, Jennifer; Sheth, Kevin N.; Woo, Daniel; Adeoye, Opeolu
<x xml:space="preserve">Abstract</x> Background and Purpose— Monocytes may contribute to secondary injury after intracerebral hemorrhage (ICH). We tested the association of absolute monocyte count with 30-day ICH case fatality in a multiethnic cohort. Methods— Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) study is a prospective, multicenter, case–control study of ICH among white, black, and Hispanic patients. In 240 adults with nontraumatic ICH within 24 hours of symptom onset, we evaluated the influence of ICH score and complete blood count components on 30-day case fatality using generalized linear models. Results— Mean age was 62.8 years (SD, 14 years); 61.7% were men, 33.3% black, and 29.6% Hispanic. Median ICH volume was 9.9 mL (interquartile range, 4.4–26.7). After adjusting for patient age and initial hemoglobin, higher total white blood cell count (P=0.0011), driven by higher absolute neutrophil count (P=0.002), was associated with larger ICH volume, whereas absolute monocyte count was not (P=0.15). After adjusting for age, Glasgow Coma Scale, ICH volume, location, and the presence or absence of intraventricular hemorrhage, baseline absolute monocyte count was independently associated with higher 30-day case-fatality (odds ratio, 5.39; 95% confidence interval, 1.87–15.49; P=0.0018), whereas absolute neutrophil count (odds ratio, 1.04; 0.46–2.32; P=0.93) and white blood cell count (odds ratio, 1.62; 0.58–4.54; P=0.36) were not. Conclusions— These data support an independent association between higher admission absolute monocyte count and 30-day case-fatality in ICH. Inquiry into monocyte-mediated pathways of inflammation and apoptosis may elucidate the basis for the observed association and may be targets for ICH neuroprotection.